Investigating general practitioner engagement with pharmacists in Home Medicines Review. Issue 5 (28th August 2015) - Costa, Daniel; Van, Connie; Abbott, Penny; Krass, Ines
Abstract: The Home Medicines Review (HMR) involves a home visit from an accredited HMR pharmacist to review a patient's medicines, and a report to the patient's general practitioner (GP) with recommendations for improving medicine management. Notwithstanding evidence supporting the benefits of medicines review, broad uptake by GPs in Australia remains low. We developed the 10-item Home Medicines Review Inventory (HMRI) to assess GP attitudes and behaviours regarding the HMR and modelled factors associated with the frequency of GP engagement with HMRs. Four items assessing frequency of behaviours and six items assessing attitudes related to HMR were answered by 180 GPs in a national GP survey. The HMRI's psychometric properties were examined with exploratory factor analysis (EFA), Rasch analysis, and correlations with related instruments. Structural equation modelling was used to evaluate factors associated with HMR-related behaviours. EFA and Rasch analysis generally supported the current format of the instrument. Attitudes to HMR, gender, previous positive experiences with pharmacists, a system for working together, and participation in joint education activities predicted frequency of HMR-related behaviours. Although GPs' attitudes to HMR were generally positive, HMR-related behaviours tended to occur with low frequency. This instrument may be used to investigate why HMR uptake has thus far been low and also help identify opportunities for building interprofessional communication and trust between GPs and pharmacists.